(untitled) (Journal of Parents and Teachers, 2026)
The Gulf War, as well as dominating the front pages of newspapers, has been a topic for discussion in schools. This section features a project carried out by the Eirís School in La Coruña, in which pupils from Years 4 and 7 of the EGB and Year 2 of the BUP took part. It consists of simple questions put to the pupils, such as: Why does war exist? Are you worried about war? Some solutions to end war. It is complemented by a number of related images created by the pupils themselves.